Epigenetic Alterations in Anesthesia-Induced Neurotoxicity in the Developing Brain - Wu, Ziyi; Zhao, Ping (Frontiers in Physiology, 2018)
Before birth and early in life, the developing brain is particularly sensitive to environmental and pharmacological influences. Increasing experimental evidence suggests that an association exists between exposure to anesthesia during a vulnerable period of brain development and subsequent poor neurodevelopmental outcomes. However, the mechanisms underlying this association are not fully understood. Epigenetics, broadly defined as the regulation of gene expression without alterations of DNA sequence, has become a field of tremendous interest in neuroscience. In recent years, a growing body of literature suggests that anesthesia-induced long-term changes in gene transcription and functional deficits in learning and behavior later in life are mediated via epigenetic modifications. This brief review provides an overview of epigenetic mechanisms and highlights the emerging roles played by epigenetic dysfunctions in the processes of anesthesia-induced neurotoxicity in the developing brain. Epigenetic targeting of DNA methyltransferases and/or histone deacetylases may have some therapeutic value. Epigenetics may lead to the identification of novel markers that contribute towards considerable translational significance in the field of neuroprotection.